2020
DOI: 10.1103/physrevfluids.5.024601
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent cascade, bottleneck, and thermalized spectrum in hyperviscous flows

Abstract: In many simulations of turbulent flows the viscous forces ν∇ 2 u are replaced by a hyper-viscous term −νp(−∇ 2 ) p u in order to suppress the effect of viscosity at the large scales. In this work we examine the effect of hyper-viscosity on decaying turbulence for values of p ranging from p = 1 (regular viscosity) up to p = 100. Our study is based on direct numerical simulations of the Taylor-Green vortex for resolutions from 512 3 to 2048 3 . Our results demonstrate that the evolution of the total energy E and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…We further demonstrate, using a shell-toshell energy transfer analysis, that this "shallow" kinetic energy spectrum is associated with magnetic tension, which acts to suppress the kinetic energy cascade and provides the major contribution in the energy flux from large to small scales. This result is in marked contrast with incompressible hydrodynamic turbulence, where the kinetic energy cascade is the only means of transferring energy between scales in a self-similar fashion (which in turn leads to the emergence of the k −5/3 scaling) and departures from this expected scaling in hydrodynamic turbulence simulations and experiments have been associated with the existence of "bottlenecks" (Falkovich 1994;Schmidt et al 2006;Frisch et al 2008;Donzis & Sreenivasan 2010;Küchler et al 2019;Agrawal et al 2020). As such, the results presented in this work demonstrate the rich physics phenomenology that can operate even in the simplest scenarios (vanishing mean field, cross-helicity, and magnetic helicity) where mag-netic tension is dynamically important and further serve to highlight the necessary ingredients that MHD turbulence theory and phenomenology should incorporate in order to explain scalings of kinetic and magnetic energy observed in both simulation and observation of magnetized turbulence.…”
Section: Introductionmentioning
confidence: 86%
“…We further demonstrate, using a shell-toshell energy transfer analysis, that this "shallow" kinetic energy spectrum is associated with magnetic tension, which acts to suppress the kinetic energy cascade and provides the major contribution in the energy flux from large to small scales. This result is in marked contrast with incompressible hydrodynamic turbulence, where the kinetic energy cascade is the only means of transferring energy between scales in a self-similar fashion (which in turn leads to the emergence of the k −5/3 scaling) and departures from this expected scaling in hydrodynamic turbulence simulations and experiments have been associated with the existence of "bottlenecks" (Falkovich 1994;Schmidt et al 2006;Frisch et al 2008;Donzis & Sreenivasan 2010;Küchler et al 2019;Agrawal et al 2020). As such, the results presented in this work demonstrate the rich physics phenomenology that can operate even in the simplest scenarios (vanishing mean field, cross-helicity, and magnetic helicity) where mag-netic tension is dynamically important and further serve to highlight the necessary ingredients that MHD turbulence theory and phenomenology should incorporate in order to explain scalings of kinetic and magnetic energy observed in both simulation and observation of magnetized turbulence.…”
Section: Introductionmentioning
confidence: 86%
“…A second possibility is of course the use of a hyperviscous term. This however has the drawback that we would end up solving not the inviscid equation but its viscous form and for higher orders of the hyperviscosity-which is similar in spirit to the idea of purging-the solutions thermalize [10,12,32]. Another approach is due to Pereira et al [18] who showed that a waveletbased filtering technique also leads to a suppression of the resonances leading to tygers.…”
mentioning
confidence: 99%
“…In an attempt to better resolve inertial ranges while forcing at intermediate and larger wavenumbers, hyperviscosity, (−1) p+1 ∇ 2p , was used in all runs and for all three fields, replacing the regular viscosity and regular magnetic diffusivity seen in (2.1a)-(2.1c). As long as the value of p is not very large, hyperviscosity has been shown to have no significant effect on the turbulent properties of 3-D turbulence, and we expect the same to be the case for our work (Agrawal et al 2020). The value of p was set to 2 in all runs except for those where k f = 32, in which case p = 4.…”
Section: Methodsmentioning
confidence: 82%